Assessing public sector organisations through performance measurement: A comparative study of New Zealand, Singapore and UK - Jones, David Seth (2003)
From the late 1980's, the governments of New Zealand, Singapore and the UK embarked upon major public sector reforms. These reforms as they were applied to the core public sector and other organisations rersponsible for public services, were broadly shaped by the principles of 'managerialism' or 'new public management'.They entailed importing into these organisations business practices associated with the private sector. The 'managerialist' reforms in both countries to a certain extent followed a similar path although in some respects they were divergent. At the heart of both sets of reforms was performance measurement.It was recognised that reforming the civil service or public service along 'managerialist' lines required accurate, precise and relevant measurement of the quantity, quality, efficiency and effectiveness of public services and programmes. Much work has been undertaken in both countries on how best this can be done. Government departments and other public agencies in New Zealand, Singapore and the UK have developed a range of performance indicators for the key areas of performance measurement and have, in many cases, set yearly targets based on those indicators.As a measure of the commitment to performance measurement and typical of many other departments in New Zealand, Department of Corrections in New Zealand now employees about 1010 output quantity and quality indicators (DCNZ 2002).'It was also recognised that for performance measurement and target setting to be an effective spur to performance, it was necessary to concomitantly introduce incentives to achieve better performance. The first part of the paper considers, in light of the reforms in three countries, the main types of performance measurement used, the setting of targets and evaluation of performance results. The second part discusses the limitations and drawbacks of performance measurement as a means for evaluating the work of public sector organisations, which has become evident in the three countries.